Pimarane Diterpenoids from Aerial Parts of Lycopus lucidus and Their Antimicrobial Activity. (4th February 2022) - Pandey, Jitendra; Hwang, Bang Yeon; Lee, Hyeong-Kyu; Poudel, Amrit
Abstract : The ethyl acetate fraction obtained from aerial parts of L. lucidus was subjected for isolation of new bioactive compounds, which enabled isolation of five new pimarane-type diterpenoids, namely, 3 β, 8 β, 12 β, 18-tetrahydroxy pimar-15-ene (10), 7 α, 8 β, 12 β, 18-tetrahydroxy pimar-15-ene (11), 3 β, 8 β, 11 β, 12 α, 18-pentahydroxy pimar-15-ene (12), 12 β acetoxy, 8 β, 3 β, 18-trihydroxy pimar-15-ene (13), and 3 β acetoxy, 8 β, 12 β, 18-trihydroxy pimar-15-ene (14), along with nine known compounds. The structures were elucidated by spectroscopic analysis and comparison with literature data. The isolated new pimarane diterpenoids were examined for antimicrobial activity against Gram-negative and Gram-positive bacteria strains. Among them, the compound 3 β, 8 β, 12 β, 18-tetrahydroxy pimar-15-ene (10) was most effective, exhibiting minimum inhibitory concentration (MIC) values of 15.62 µg/mL against Staphylococcus epidermidis, 31.25  µ g/mL against Staphylococcus aureus, 62.5  µ g/mL against Pseudomonas aeruginosa, and 125  µ g/mL against Escherichia coli .